THE ROLE OF WOMEN IN THE DEVELOPMENT OF KOKAN LITERARY ENVIRONMENT (Scientific journal of the Fergana State University, 2026)
This article examines the work of women scientists and poets who made a great contribution to the spiritual development of the Uzbek people during the period of the Kokan Khanate and in later periods. In particular, the contribution of such poets as Uvaysiy, Nadira, Dilshadatin, Makhzuna, Anbaratin to the development of the literary environment of Kokand is analyzed in detail.